Document Design - Ricky Telg (EDIS, 2012)
Document design is the process of choosing how to present all of the basic document elements, so your document’s message is clear and effective. When a document is well designed, readers understand the information more quickly and easily. Readers feel more positive about the topic and more accepting of its message. This 3-page fact sheet was written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.